2022
DOI: 10.1007/s11205-022-02877-x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Social, Economic, and Environmental Indicators’ Effects on Public Health and Health Inequality Globally: From the Perspective of Vulnerability

Abstract: Public health and health inequality have been widely researched as they are essential for human development and social justice. Although factors influencing public health and health inequality have been explored, an integrated and comprehensive analysis of social, economic, and environmental indicators’ effects on public health and health inequality globally is yet to be conducted. The current study addresses this gap by using a theoretical framework that integrates these three dimensions, examining their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…These studies have shown that animals in lower hierarchical positions or with restricted access to resources exhibit higher levels of stress and are more prone to engage in drug-seeking behaviors. This mirrors findings in human populations, where individuals facing economic hardship and social marginalization are at a higher risk for developing addiction [59,60].…”
Section: Economic and Social Inequality Addiction Risk Factorssupporting
confidence: 72%
“…These studies have shown that animals in lower hierarchical positions or with restricted access to resources exhibit higher levels of stress and are more prone to engage in drug-seeking behaviors. This mirrors findings in human populations, where individuals facing economic hardship and social marginalization are at a higher risk for developing addiction [59,60].…”
Section: Economic and Social Inequality Addiction Risk Factorssupporting
confidence: 72%
“…However, accurately quantifying social vulnerability remains a challenge, and the COVID-19 pandemic has highlighted a critical need to identify those most eligible and provide support to mitigate risks, such as understanding the relationship between social vulnerability and SARS-CoV-2 incidence. It is critical to understand the interplay between social determinants and implement risk mitigation guidelines that can reduce the spread of infectious diseases [21,22].…”
Section: Construction Of the Potential Epidemic Vulnerability Indexmentioning
confidence: 99%
“…The second category is social factors, where socioeconomic factors are considered fundamental factors affecting health inequalities [ 38 ]. The impact of different socioeconomic conditions on health inequalities has been demonstrated, and it has been found that increased income disparity leads to unhealthy habits, lack of material resources, and shortage of social capital in low-income groups [ 39 , 40 ], and negative emotions such as depression and loneliness in low-income groups also increase with age [ 41 , 42 ].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%